THE IMPACT OF WORLD WAR I ON ENGLISH LITERATURE (POETRY) - Sevil Alasgar gizi Mammadova (Research Focus International Scientific Journal, 2025)
the First World War (1914–1918) radically changed not only political and social systems, but also literature. In English literature, this war created a powerful stage that reflected moments of trauma, loss, heroism, and the breaking of human psychology. War poets — Wilfred Owen, Siegfried Sassoon, Rupert Brooke, and others — shattered the traditional image of romantic heroism and showed the real horrors of war. In prose, authors such as Erich Maria Remarque (although German, his influence reached British writers), Virginia Woolf, and D.H. Lawrence described the devastating effects of war on society and the individual. The First World War radically changed English literature, destroying romantic images of war and giving rise to realistic, often pacifist positions. Wilfred Owen’s poem "Dulce et Decorum Est" refutes the traditional heroic idea of ​​war, while Siegfried Sassoon’s poetry sharply criticizes society’s indifference to war. Ford Madox Ford’s novel Parade’s End delicately reflects the disintegration of society, and Virginia Woolf’s Mrs Dalloway delicately reflects the post-war psychological crisis. T.S. Eliot’s poem The Waste Land has become a symbol of the moral collapse of an entire Europe. These works show that the war left a deep mark on English literature not only as a historical event, but also as a shaking of humanity, culture and morality.